2020
DOI: 10.29309/tpmj/2020.27.09.4175
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of calcium hydroxide and chlorhexidine gel as intracanal medicament in relieving interappointment pain: Effect of gender and age.

Abstract: Objectives: This study was done to compare calcium hydroxide (Ca(OH)2) and chlorhexidine (CHX) in relieving interappointment pain, in addition to observe influence of gender and age. Study Design: Randomized Control trial. Setting: Department of Operative Dentistry, Fatima Memorial Hospital, Lahore. Period: 3rd October 2016 to 20th May 2017. Material & Methods: 100 subjects were divided into 2 groups of 50, group A (Ca(OH)2) and group B (CHX). Information was recorded regarding the gender, age, intracanal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…1 Odontogenic pain usually occurs due to decayed tooth, trauma, infections and after post endodontic treatment. 2 In spite of recent advances in management of pain, previous study reported the prevalence of postoperative pain ranging from 3-58%. 3 Microbes play a critical role in the pathogenesis of periapical and periodontal disease; thus, their complete removal is the key to success for root canal treatment.…”
Section: Introductionmentioning
confidence: 99%
“…1 Odontogenic pain usually occurs due to decayed tooth, trauma, infections and after post endodontic treatment. 2 In spite of recent advances in management of pain, previous study reported the prevalence of postoperative pain ranging from 3-58%. 3 Microbes play a critical role in the pathogenesis of periapical and periodontal disease; thus, their complete removal is the key to success for root canal treatment.…”
Section: Introductionmentioning
confidence: 99%